Two-portal versus three-port video-assist thoracoscopic surgery for early stage nonsmall cell lung cancer: A retrospective study. Issue 33 (August 2017) - Yan, Xiaokun; Chen, Xiaochun; Li, Guangbin; Chen, Shaomu
Abstract : Abstract: This study was conducted to compare the perioperative outcomes of two-portal and three-port video-assist thoracoscopic surgery (VATS) for early stage nonsmall cell lung cancer. In this retrospective analysis, 279 cases of two-port VATS with a single utility port and 152 cases of three-port VATS performed by our department from October 2010 to December 2014 were collected. The operative time, volume of intraoperative blood loss, number of dissected lymph nodes, volume of postoperative pleural drainage, postoperative extubation time, and duration of postoperative hospitalization were compared between these 2 groups. No statistically significant differences on the operative time, volume of postoperative bleed, and the number of dissected lymph nodes was noted between two-port and three-port video-assist thoracoscopic surgery. Less postoperative pleural drainage, shorter extubation time, and postoperative hospitalization were observed in the two-port VATS group when compared with those of three-port VTAS group Two-port VATS decreased operative postoperative pleural drainage and resulted in shorter extubation time and postoperative hospitalization compared with three-port VATS. Two-port VATS is a safe and feasible approach for early stage nonsmall cell lung cancer.